Analysis of Age Factor and Hemoglobin Profiles in The Incidence of Uterine Leiomyoma - Paramarta, Nugrahani Putri Tyas; Kurniati, Yuni Prastyo (Jurnal Kesehatan, 2025)
Uterine leiomyoma is recognized as the most common benign tumor of the female reproductive system and remains a significant cause of gynecological morbidity worldwide. Its development has been closely associated with hormonal exposure, particularly estrogen and progesterone, and with reproductive age. Despite being frequently encountered in clinical practice, the role of other contributing factors, such as hemoglobin status, remains less clear. This study examined the relationships among age, hemoglobin concentration, and the incidence of uterine leiomyoma. An observational-analytic case-control design, using leiomyoma as cases and adenomyosis as controls, was conducted at PKU Muhammadiyah Hospital, Surakarta. A total of 246 participants were included, comprising 93 women with histopathologically confirmed leiomyoma and 153 women with adenomyosis as the control group. Data were obtained from hospital medical records, and statistical analyses were performed using Chi-square tests followed by logistic regression. The results demonstrated that being in the reproductive age group (≤50 years) significantly increased the likelihood of leiomyoma occurrence (OR=3.114, 95%CI: 1.141–8.500, p=0.021). In contrast, hemoglobin profiles did not show a significant association with leiomyoma incidence (OR=0.777, 95%CI: 0.428–1.441, p=0.407). Although anemia was frequently observed in both groups, it appeared more likely to be a clinical manifestation of abnormal uterine bleeding than a direct etiological factor.